Growing soybeans after green and organic manure - Tanaka, Roberto Tetsuo; Mascarenhas, Hipólito Assunção Antônio; Dias, Otávio Souza; Campidelli, Cláudio; Bulisani, Eduardo Antônio (Pesquisa Agropecuaria Brasileira, 1992)
During the 1987/89 growing seasons two experiments were carried out in a Red-Yellow Latosol (Oxisol) sandy phase of low fertility to verify the effect of incorporated chicken manure and these four green manure crops: velvet bean (Mucuna aterrima (Piper & Tracy) Holland), sunn hemp (Crotalaria juncea L.), (Dolichos lab-lab L.) and pigeon pea (Cajanus cajan (L.) Millsp.) on the yield of soybean (Glycine max (L.) Merrill). The check treatment was continuous soybean crop. The yield of green manure (fresh weight) varied from 12.3 t/ha for sunn hemp to 36.5 t/ha for velvet bean. In spite of the low sunn hemp yield, the average of soybean yield at the two locations was highest after this previous crop, and no difference on yield were obtained between plots where the previous crop was velvet bean and chicken manure was applied. The soybean yields after Dolichos lab-lab or pigeon pea were no different to that of continuous soybean plots.